(untitled) (Research, Society and Development, 2021)
Introduction: There is a growing demand for facial harmonization, with the adoption of facial aesthetic procedures, for example, the use of facial fillers such as silicone, polymethylmethacrylate (PMMA) and hyaluronic acid. However, professionals who apply these products must know well all types of fillers so that they can prevent future problems. Likewise, let them know about the importance of the ultrasound exam as a primordial procedure to help in the resolution of damages. Objective: To present how ultrasonography is essential for the application of facial fillers, as well as for treating harmful effects to the face due to complications. Methodology: It is a case study with a qualitative, descriptive approach, carried out in a dentistry office. Case report: A 57-year-old female patient sought dental care to perform facial harmonization with filling the chin, one month later she complained of a globular mass in the submental region. Conclusion: The ultrasound examination was crucial to confirm that the facial filler, hyaluronic acid, did not slip. A solid hypoechoic image was identified on the USG. Knowledge of facial fillers assured the professional to discard the hypothesis of hyaluronic acid migration.